2015
DOI: 10.1016/j.drugalcdep.2015.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate and event-level associations between substance use and sexual behavior among gay and bisexual men: Comparing retrospective and prospective data

Abstract: Background Despite limited research, some evidence suggests that examining substance use at multiple levels may be of greater utility in predicting sexual behavior than utilizing one level of measurement, particularly when investigating different substances simultaneously. We aimed to examine aggregated and event-level associations between three forms of substance use—alcohol, marijuana, and club drugs—and two sexual behavior outcomes—sexual engagement and condomless anal sex (CAS). Method Analyses focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 41 publications
3
48
1
1
Order By: Relevance
“…Contrary to previous studies showing higher rates of substance use among HIV-positive MSM (Parsons et al, 2014; Parsons and Starks, 2014; Rendina et al, 2015) and transgender populations (Mayer et al, 2016), our results found these two groups had lower percentages of substance use overall (27.4% and 26.1%, respectively) compared to men who have sex with women (37.4%) and female (30.5%). It is worth noting that the information on sexual orientation being an essential element of self-identification was not recorded in the EMRs used for analyzing this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous studies showing higher rates of substance use among HIV-positive MSM (Parsons et al, 2014; Parsons and Starks, 2014; Rendina et al, 2015) and transgender populations (Mayer et al, 2016), our results found these two groups had lower percentages of substance use overall (27.4% and 26.1%, respectively) compared to men who have sex with women (37.4%) and female (30.5%). It is worth noting that the information on sexual orientation being an essential element of self-identification was not recorded in the EMRs used for analyzing this study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, condomless anal intercourse among MSM seems to vary by the type of drug and the frequency of use [58]. It has been suggested that frequent alcohol and drug use are common in urban gay male culture [59].…”
Section: Discussionmentioning
confidence: 99%
“…The TLFB demonstrates strong reliability and validity, including agreement with real-time interviews and collateral reports of alcohol use [69] and sex risk [70], and has previously been utilized with HIV-positive GBM [7173] and GBM with SC [9, 26, 74, 75]. From the TLFB we calculated: (1) the total number of new (i.e., first-time) male partners men had as an indicator of frequency of sexual partnering; (2) the total number of CAS acts with any non-main (i.e., casual) male partners as an indicator of TRB; and (3) the total number of days on which club drugs (i.e., cocaine/crack, crystal methamphetamine, ecstasy/MDMA, ketamine, and GHB) were used as an indicator of substance use frequency.…”
Section: Methodsmentioning
confidence: 99%